O trabalho pedagógico de professores gays e bissexuais: receio docente, resistência e esperança na Escola pública (Uberlândia – 2012-2022) - Schnekenberg, Guilherme Fernando (2022)
The dissertation here presented is result of a researh realized conducted on the Master’s degree of the Post-Graduated Program em Education of Federal University of Uberlândia. Our investigation had in the center of its analyses the impact in school routine of the conflicts related to sexual and gender diversity in brazilian society. The researchwas attended by six teachers, who gave interviews as LGBT teachers in the basic education network over the last decade. We chose Oral History as a research metodology, considering its analytical contributions to understand the experience of teachers, between theis professional routine and the way they elaborate it. Thus, the research was mediated by theoretical contributions from authors like Edward P. Thompson, Rogério Junqueira, Luis Felipe Miguel, Guacira Lopes Louro, Karl Marx, Claudia Vianna, Dermeval Saviani and Tomaz Tadeu da Silva. We used the dialogue between historical-dialectical materialism and the field of gender studies, promoting a meeting between analysis and categories that allow understanding life and labor conditions of LGBT teachers from Uberlândia city. Based on those perspectives, we discuss how teacher criminalization and the creation of moral panics help the construction of a teacher fear among basic education workers. With that concept of Teaching Fear we demarcate not only the action and processes of persecution against teachers, but especially the feeling they produce and its elaboration among the interviewed teachers. The categorie of experience is one of the means of acessing the experience of that group of teachers, considering the information and the analysis they elaborate and presented in the interviews. Therefore, we take the inseparability between social relations and consciousness produced by LGBT teachers in the many processes they’re involved. In addition to an analysis of the tensions and conflicts of recent decades, the teachers algo talk about possibilities of resistance and positive changes in the generations that occupy the school nowadays. Thus, the dissertation points to the contradiction that mediates the processes we analyze: attacks against teachers and the varioues forms and needs of maintenance of sexual and gender diversity at classrooms. With this contradiction before our eyes, the research presents an analysis of the presence of sexual and gender diversity in school, facing attempts to maintain a conservative morality about body and sexuality, and the ways of confrontation produced by LGBT community at school.